Internet-Based i-Karier Literacy to Increase Parental Support in Adolescents’ Career Decision-Making: [Literasi i-Karier Berbasis Internet untuk Meningkatkan Dukungan Orang Tua dalam Pengambilan Keputusan Karir Remaja] - Zakiyah Rahmani; Hastjarjo, Thomas Dicky (ANIMA Indonesian Psychological Journal, 2022)
In a collective culture, parental career support is considered an important source of consideration for adolescent students. Unfortunately, preliminary research conducted by the authors found that parents were not quite able to provide the support their children required. One of the efforts to overcome this problem is the provision of psychoeducation to increase career decision-making literacy to parents through an application named i-Karier. This study tested a hypothesis that i-Karier literacy can increase parental support in adolescent students’ decision-making. This study utilized a quantitative approach with quasi-experimental design (untreated control group design with dependent pretest and posttest samples using a double pretest). The participants were 48 parents of high school students in Class XI and XII who were selected using purposive sampling. There were nine inclusion criteria, namely: (1) education level; (2) children’s career aspirations; (3) parents’ location; (4) zero attendance in training on adolescents' career decision-making; (5) ability to operate a smartphone; (6) availability of supporting facilities; (7) low to moderate levels of knowledge of career decisions; (8) low to moderate scores on the parental support scale; and (9) parents' willingness to participate. The results of mixed Analysis of Variance (ANOVA) model reported a significant interaction between group factors and measurement period factors on parental support, F(2.01, 92.51) = 130.99, p < .01, η_p^2= .74. The results of the interview regarding intervention effectiveness to participants in the experimental group confirmed these findings. Fundamentally, participation in this program could improve the ability of parents to provide the support their children require when facing various major choices in higher education. Dalam budaya kolektif, dukungan orang tua dalam pengambilan keputusan karier (parental career support) dianggap sebagai sumber pertimbangan penting bagi siswa remaja. Sayangnya, penelitian awal yang dilakukan oleh penulis menemukan bahwa para orang tua kurang dapat memberikan dukungan yang dibutuhkan oleh anak-anak mereka. Salah satu upaya untuk mengatasi masalah tersebut adalah pemberian psikoedukasi untuk meningkatkan literasi pengambilan keputusan karier kepada para orang tua melalui aplikasi bernama i-Karier. Penelitian ini menguji sebuah hipotesis bahwa literasi i-Karier dapat meningkatkan dukungan orang tua dalam pengambilan keputusan siswa remaja. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi-experiment (untreated control group design with dependent pretest and posttest samples using a double pretest). Partisipan penelitian ini adalah 48 orang tua siswa Sekolah Menengah Atas (SMA) Kelas XI dan XII yang dipilih menggunakan purposive sampling. Terdapat sembilan kriteria inklusi yaitu: (1) tingkat pendidikan; (2) aspirasi karier anak; (3) lokasi orang tua; (4) tidak pernah mengikuti pelatihan; (5) kemampuan mengoperasikan smarphone; (6) memiliki fasilitas mendukung; (7) memiliki pengetahuan keputusan karier; (8) skor parental support scale; dan (9) kesediaan orang tua untuk berpartisipasi. Hasil analisis model Analysis of Variance (ANOVA) campuran melaporkan adanya interaksi yang signifikan antara faktor kelompok dan faktor periode pengukuran terhadap dukungan orangtua, F(2,01, 92,51) = 130,99; p < 0,01; η_p^2 = 0,74. Hasil wawancara perihal efektivitas intervensi kepada para partisipan di kelompok eksperimen mengonfirmasi temuan tersebut. Secara mendasar, keikutsertaan dalam program ini dapat meningkatkan kemampuan para orangtua dalam memberikan dukungan yang dibutuhkan oleh anak-anak mereka saat menghadapi berbagai pilihan jurusan di pendidikan tinggi.